Challenges in Teaching English Consonant Clusters to Non-Native Speakers: A Phonological Approach - Permata, Divia Atma; Sabil, Salsabila; Rohmana, Wahyu Indah Mala (Indonesian Journal of English Language Studies (IJELS), 2025)
This study explores how non-native English speakers, especially Indonesian learners, pronounce consonant clusters. Differences in their native phonological systems often cause these difficulties, leading to the addition of vowels or the omission of consonants, which impacts communication. The purpose of this study is to understand non-native speakers’ challenges when pronouncing consonant clusters in English. In addition, it also aims to find effective methods to address these issues. This qualitative descriptive study explored the phonological issues of consonant clusters taught by English teachers to non-native speakers. The data were collected through an online Google Forms survey that asked teachers about their experiences, opinions, and teaching methods. Only half of the twenty English teachers had received specific phonological training, and the majority had limited teaching experience, according to the survey. The results suggested that to improve pronunciation, more targeted teaching strategies such as phonetic drills and the use of multimedia tools are needed. Slow sound repetition and audio or video examples, which were the teaching methods evaluated, were found effective. Sound repetition was slightly preferred because of its active practice approach. This study emphasizes the importance of instruction tailored to students' needs and suggests the use of technology to improve the quality. Through a flexible and adaptive approach, it is hoped that students’ English language skills can improve significantly.